Geranylgeraniol (GGOH) as a Mevalonate Pathway Activator in the Rescue of Bone Cells Treated with Zoledronic Acid: An In Vitro Study - Riham M. Fliefel; Saleh A. Entekhabi; Michael Ehrenfeld; Sven Otto (Stem Cells International)
Bisphosphonates (BPs) are the keystone to treat bone disorders. Despite the great benefits of BPs, medication-related osteonecrosis of the jaw (MRONJ) arouse as a potential side effect. Nitrogen-containing BPs (N-BPs) as zoledronate (ZA) act by the inhibition of specific enzymes of the mevalonate pathway resulting in altering protein prenylation which is required for the posttranslational maturation of the small GTP-binding proteins. Geranylgeraniol (GGOH) is an intermediate product in the mevalonate pathway having positive effects on different cell types treated with BPs by salvaging protein prenylation improving cell viability and proliferation in tissue regeneration, thus overcoming N-BP-induced apoptosis. Here, the effect of different concentrations of zoledronate (ZA) on the bone cells has been investigated by cell viability assay, live/dead staining, and western blot to understand if GGOH was able to rescue bone cells and levels of statistical significance were indicated at ∗P<0.05, ∗∗P<0.01, ∗∗∗P<0.001, and ∗∗∗∗P<0.0001. Although the high concentration of ZA had significantly decreased the cell viability in the bone cells, GGOH reversed the action of ZA on the cells while at very high concentration; it caused severe reduction in the cell viability. Rap1A, a member of the GTPases family, was expressed in the negative controls but was absent in cells treated with high concentrations of ZA. The addition of GGOH had increased the expression of Rap1A up to a certain limit. The experiments proved that ZA acts directly on the mevalonate pathway and protein prenylation and that GGOH could be applied as a future local therapy to MRONJ.